Studi Atas Manhaj Tarjih Muhammadiyah dan Aplikasinya dalam Istinbath Hukum - SA, Romli; Afriansyah, Syafran (Jayapangus Press, 2023)
This research aims to analyze the formulation and basis for the formation of Manhaj Tarjih Muhammadiyah. This type of research is qualitative with a literature study approach. Data analysis uses content analysis and comparative approaches. This research found that first, the basis for the formulation of the Muhammadiyah Tarjih Council's Manhaj in legal istinbath was sourced from the Al-Qur’an and al-Sunnah as well as the results of the ijtihad of the ulama. Second, the approach used by the Muhammadiyah Tarjih Council in understanding the texts of the Al-Qur’an and al-Sunnah is through the Qawa'id lughawiyah texts. And third, facing problems for which there is no text, the Muhammadiyah Tarjih Council uses a general approach to the meaning of the texts of the Koran and al-Sunnah, an istidlal approach with various tools/media according to the problems that arise; such as using the istislahi approach and/or the qiyasi approach. Likewise, using qawaid fiqhiyah in dealing with various problems, especially new problems for which the legal provisions are completely unclear.